Decision Support System to Determine the Number of Production Tofu using the Fuzzy Sugeno Method (Case Study: Home Industries Tofu in Seyegan District) - Indrianingsih, Yuliani (Institut Teknologi Dirgantara Adisutjipto, 2018)
The production process is a way to increase the usefulness of an item and service using existing production factors. The decision making process to determine the amount of production, especially in the business world contains risks. It needs to be supported by careful calculations so that the risk of loss can be avoided. Industri associations tofu